Alley cropping as an alternative under changing climate and risk scenarios: A Monte-Carlo simulation approach. (November 2020) - Cary, Michael A.; Frey, Gregory E.
Abstract: Alley cropping is an agroforestry system in which annual crops are grown in alleys between rows of woody perennials for timber or other products, which can provide ecosystem services and help farmers diversify outputs. But is alley cropping a financially viable alternative to monocropping? To answer this question, a Monte Carlo model of financial risk and returns was used to understand how this diversification of outputs might help farmers in the southeast United States adapt to future scenarios in which agriculture or forestry may become more risky due to a changing climate or other factors. Traditional monocropping had the highest mean returns in the base scenario (based on current risk conditions), but the highest risk. Pine plantations had the lowest returns and lowest risk, and alley cropping was intermediate (mean soil expectation values of $5513 for monocropping, $3955 for alley cropping, and $2693 for pine plantations). The model results showed that traditional monocropping does not stochastically dominate alley cropping in any of the risk scenarios, meaning that alley cropping may have a place for risk-averse farmers. Furthermore, in the scenario in which the downside risk of annual crop production is increased – perhaps due to increased frequency of floods, droughts, etc. – alley cropping mean returns are higher and risk lower than traditional monocropping (mean soil expectation values of $2951 and $2911, respectively, and pine plantations at $2688), meaning any risk averse farmer might prefer alley cropping to monocropping. Highlights: Simulated returns from alley cropping, monocropping, and pine plantations under six potential future climate scenarios. Risk averse land managers may prefer alley cropping. In scenarios with an increased catastrophe probability, returns from alley cropping met or exceeded returns from monocropping.